Mining Externalities in Indonesia and Their Implications for Sustainable Development: A Systematic Literature Review - Djuanda Hatta; Musa; Fatmawati Fatmawati (Indonesian Journal Publisher, 2026)
The review identifies consistent environmental impacts, including accelerated deforestation, hydrological degradation, heavy-metal contamination, and persistent post-mining land damage. Social externalities are reflected in rising respiratory and waterborne diseases, livelihood disruptions among agrarian and coastal communities, and recurrent conflicts linked to land tenure disputes and weak recognition of indigenous rights. Economic externalities manifest through unequal benefit distribution, long-term public costs for health and ecosystem restoration, and short-lived employment dominated by non-local workers. Weak regulatory enforcement and short-term, poorly targeted corporate social responsibility (CSR) programs further exacerbate these issues. Overall, the findings reveal a structural imbalance between economic gains and socio-ecological risks in Indonesia’s extractive sector. The study proposes policy pathways to strengthen environmental governance, internalize external costs, improve community welfare, and support a transition toward sustainable mineral development.